Pengaruh Suasana, Kualitas Makanan, dan Persepsi Nilai terhadap Kepuasan Pelanggan Rumah Makan Goa Sumbawa - Maradita, Fendy; Susilawati, Mega (Jurnal Nasional Manajemen Pemasaran dan SDM, 2021)
This study aims to find out the influence of atmosphere, food quality, and perception of value on customer satisfaction. This research uses a type of Quantitative Associative research. The data collection method was carried out by distributing questionnaires to 100 respondents, namely customers at Sumbawa Goa Restaurant. Sampling techniques using non probability sampling and purposive sampling. Data analysis used is multiple linear regression analysis. Based on the results of the study, it can be concluded that the three free variables namely atmosphere, food quality and value perception have a positive and significant influence on restaurant customer satisfaction.